A systematic literature review of teachers' beliefs on play in contemporary education. (1st June 2018) - Woods, Francesca; Bond, Caroline
Abstract : The United Nations Convention on the Rights of the Child (UNCRC) has responded to research highlighting the decline in children's access to play through the addition of General Comment No 17 to Article 31. Internationally, children spend much of their time in childcare and school settings, suggesting that teachers are well placed to protect the child's right to play. Further research has highlighted the impact of teachers' beliefs on their practice. This systematic literature review explores teachers' beliefs around play internationally. Three databases were searched between October 2016 and January 2017 yielding 9, 792 hits for screening. Thirty studies met eligibility criteria and were assessed for methodological quality and appropriateness of focus. Eleven remaining studies were included in the final review. Findings reflect tensions within teachers' definitions of play, and highlight beliefs on topical sub-types of play. Limitations and implications for practice are discussed.